Low-energy lunar trajectory design - Parker, Jeffrey S.; Anderson, Rodney L. (Hoboken, New Jersey : Wiley, 2014)
"Based on years of research conducted at the NASA Jet Propulsion Laboratory, Low-Energy Lunar Trajectory Design provides high-level information to mission managers and detailed information to mission designers about low-energy transfers between Earth and the moon. The book answers high-level questions about the availability and performance of such transfers in any given month and year. Low-energy lunar transfers are compared with various other types of transfers, and placed within the context of historical missions. Using this book, designers may reconstruct any transfer described therein, as well as design similar transfers with particular design parameters." --
6.7 Spacecraft Systems DesignAppendix A: Locating the Lagrange Points; A.1 Introduction; A.2 Setting Up The System; A.3 Triangular Points; A.4 Collinear Points; A.5 Algorithms; References; Terms; Constants; Index
Includes index.
Description based on print version record and CIP data provided by publisher.
Includes bibliographical references and index.
Keywords: Lunar probes -- Trajectories; Space flight to the moon -- Cost control; TECHNOLOGY & ENGINEERING -- Engineering (General); Electronic books; Electronic books